Pengaruh Pemberitaan Kompas.Com Terhadap Sikap Pemilih Pemula di Universitas Garut - Mustopa, Ridwan; Adnan, Iis Zilfah; Azzahra, Nedia (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
This study examines the influence of Kompas.com news on the attitudes of novice voters at the University of Garut concerning the Constitutional Court's decision on the age limit for candidates in the 2024 presidential election. The Constitutional Court's decision has sparked widespread public debate, particularly among novice voters. Given their need to understand the issue, these voters often turn to news platforms like Kompas.com, which has published over 100 articles on the subject. The study employs a quantitative research method with a descriptive approach. The sample comprises 97 novice voters from the University of Garut, selected using the purposive sampling technique. Data collection involved distributing questionnaires, while analysis included research instrument tests, linear regression analysis, and hypothesis testing. Results indicate that Kompas.com news significantly impacts voters' cognitive attitudes, with an average score of 76.9%, categorized as "good." This suggests that the news effectively enhances knowledge and understanding of the Constitutional Court’s decision. The impact on affective attitudes scores highest at 78.4%, also in the "good" category, demonstrating that the news shapes feelings and evaluations regarding the decision. Conversely, the lowest score of 76.7% pertains to conative attitudes, indicating that while respondents exhibit awareness and readiness to act upon the decision, this aspect is slightly less influenced. Overall, the findings reveal that Kompas.com news plays a substantial role in shaping cognitive, affective, and conative attitudes of novice voters toward the Constitutional Court's decision, underscoring its importance in influencing voter perspectives.